SEDIMENT DISTRIBUTION ANALYSIS IN BALOHAN BAY, SABANG - Syahrul Purnawan; Tengku Putra Fajran Alamsyah; Ichsan Setiawan; . Rizwan; Maria Ulfah; Sayyid Afdhal El Rahimi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
We investigated the sediment properties and distribution in Balohan Bay, which is located in southern Weh Island, Aceh Province. The aim of this research was to clarify the sediment distribution mechanism in the Balohan Bay using a statistical approach. Samples were collected on January 2016 using coring method. Sediment grain-size distribution from 14 stations was obtained using wet sieve analysis. A large amount of fine sand and very fine sand were found in Balohan Bay, as a result of several tributaries discharged in those areas. The sediment distribution in eastern stations showed an indication as a coarser size and a poorer sorted area, as they were adjacent to the steep cliff.